1996
DOI: 10.1093/ee/25.2.268
|View full text |Cite
|
Sign up to set email alerts
|

Trap Response and Fruit Damage by Obliquebanded Leafroller (Lepidoptera: Tortricidae) in Pheromone-Treated Apple Orchards in New York

Abstract: Pheromone disruptants were tested from 1989 to 1992 in western New York to determine effect on trap catch and potential use in the control of obliqueblmded leafroller. Clwristoneurct rosacearw (Harris), using polyethylene tube tie and controlled-release membrane dispensers in plots of 0.2-2.4 ha. Effectiveness of pheromone at different application rates and canopy locations was evaluated using synthetic pheromone-baited traps, molassesbaited traps, and by inspecting foliar terminals and fruit for leafroller da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 14 publications
1
37
0
Order By: Relevance
“…Similarly, Agnello et al (1996) found no difference in the level of disruption by using dispensers loaded with either a 94:6 Z:Ell-14:0Ac blend or a 90:5:5 Z:Ell-14:0Ac: Zll-14:0H blend in New York.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, Agnello et al (1996) found no difference in the level of disruption by using dispensers loaded with either a 94:6 Z:Ell-14:0Ac blend or a 90:5:5 Z:Ell-14:0Ac: Zll-14:0H blend in New York.…”
Section: Discussionmentioning
confidence: 94%
“…The experimental use of sex pheromones to disrupt C. rosaceana adult communication was first reported by Reissig et al (1978) and more recently by Agnello et al (1996) and Lawson et al (1996) in New York.…”
mentioning
confidence: 99%
“…The delta trap is slightly more expensive ($4.68 per set) than wing trap ($3.35 per set), but this initial higher cost may be offset because the delta type is more durable and can be reused over multiple seasons. Pheromone mating disruption is increasingly being evaluated as a pest management strategy against leafrollers and other moth pests in North America (Deland et al 1994;Agnello et al 1996;Lawson et al 1996;Shorey and Gerber 1996;Fadamiro et al 1998Fadamiro et al , 1999Isaacs et al 1999). The western lure should provide better mating disruption of C. rosaceana in Minnesota, although the notion that higher mating disruption efÞcacy will result from the use of optimal blend needs to be investigated.…”
Section: Resultsmentioning
confidence: 99%
“…However, the pheromone blends of these species are further differentiated by other minor components; these include (Z)-11-tetradecenol and (Z)-11-tetradecenal in the obliquebanded leafroller blend (El-Sayed et al, 2003) and dodecyl acetate in the redbanded leafroller blend . Control of redbanded leafroller by mating disruption using synthetic pheromones has been judged successful Novak et al, 1978;Novak & Roelofs, 1985;Cardé & Minks, 1995); however, results have been inconsistent for the obliquebanded leafroller Agnello et al, 1996;Lawson et al, 1996). Greater success has been recorded with a Western population of obliquebanded leafroller in British Columbia, Canada (Evenden et al, 1999a,b).…”
Section: Introductionmentioning
confidence: 99%